Is systemic lupus erythematosus a new risk factor for atherosclerosis? - Freire, Beatriz Funayama Alvarenga [UNESP]; Da Silva, Rogério Cardoso [UNESP]; Fabro, Alexandre Todorovic [UNESP]; Dos Santos, Daniela Cristina [UNESP] (My University, 2006)
OBJECTIVE: To evaluate the prevalence of cardiovascular events (CVE) secondary to atherosclerosis in lupus patients and correlate them to the traditional risk factors, disease duration and drug therapy used. METHODS: A retrospective study was carried out based on data obtained from patients' charts. Patients included were those who had a lupus diagnosis confirmed at least two years before inclusion in the study and had been followed since 1992. CVE were characterized as MI, angina pectoris and stroke non-related to lupus activity. Risk factors and drugs used for treatment were recorded. RESULTS: Seventy-one charts were analyzed. Patients' mean age was 34.2±12.7 years; 68 were women and three were men; 58 were Caucasian (81.6%). Ten (14.08%) presented CVE. Patients in whom CVE were observed were older (42.7 vs. 32.8 years p=0.0021) and presented longer disease duration (10.8 vs. 7.2 years p=0.011). The traditional risk factors, daily and cumulative doses of steroids, immunosuppressive drugs and antimalarial drugs were not significant when patients with and without CVE were compared. CONCLUSION: The prevalence of CVE secondary to atherosclerosis in systemic lupus erythematosus (SLE) was 14.08%. The traditional risk factors were not associated with the development of CVE in lupus patients. Patients that presented cardiovascular events were older and presented longer disease duration. It is a premature conclusion to establish SLE as an independent risk factor for atherosclerosis development.
Lupus eritematoso sistêmico: Novo fator de risco para aterosclerose?
Keywords: Atherosclerosis; Cardiovascular disease; Systemic lupus erythematosus